Substance use and lifestyle risk factors for somatic disorders among psychiatric patients in Greenland - Ida Margrethe Nielsen; Lisbeth Uhrskov Sørensen; Søren Wichmand; Parnûna Heilmann; Michael Lynge Pedersen (International Journal of Circumpolar Health)
Patients with psychotic disorders exhibit elevated mortality and morbidity rates compared to the general population primarily due to comorbid somatic diseases. This study aims to describe the prevalence of selected risk factors and somatic disorders among psychiatric patients with a diagnosis of psychotic disorder. Material and methods: Data were retrieved from Greenland’s nationwide electronic medical record. The study population consists of 104 patients diagnosed with a psychotic disorder, encompassing schizophrenia or schizotypal and delusional disorders, residing in Nuuk. The study population comprised 104 patients (68 males and 36 females) with a mean age of 40 years. More than 80% were daily smokers, and 68% had harmful use of cannabis. More than half had dyslipidemia (any imbalance in lipids), while over a quarter were classified as obese with body mass index of 30 kg/m2 or higher. Eighteen percent had hypertension, and six percent suffered from diabetes. This study revealed a notable prevalence of risk factors for somatic diseases, particularly smoking and cannabis use among patients with schizophrenia in Nuuk, indicating that a high prevalence of somatic diseases might be expected as the population gets older and the risk of developing somatic diseases becomes greater. Increased focus on monitoring and preventing those as part of the health care is recommended.